Binge drinking and illicit drug use among high school students - Raposo, Jakelline Cipriano dos Santos (2016)
Introduction: Binge drinking impairs judgment capacity and can lead to illicit drugs use among adolescents. Objectives: Investigate the association between binge drinking and use of illicit drugs (marijuana, cocaine and inhalants) among high school students. Materials and Methods: Cross-sectional study with 175 students, from both genders, enrolled in public high school in a two-stage cluster sampling, drawing schools and classes, respectively. Data were collected in April 2014 in five schools, using the validated Portuguese version of the Youth Risk Behavior Survey. Modules were used on alcohol consumption, use of marijuana and other drugs. Descriptive and inferential analyses were carried out with frequencies distribution, using chi-square test. Results: Most of the students were female (56.7%), aged 16-19 years (70.2%), regularly enrolled students (80.7%) and with family income above minimum wage (54.3%). Binge drinking, inhalants and cocaine use showed no significant difference between the sexes (p>0.05), unlike marijuana use, which was higher on boys (p<0.05). All drug use patterns were associated with binge drinking. Conclusion: The practice of binge drinking among adolescents was associated with marijuana use, as well as cocaine and inhalants.